ANALISIS PERAN MONITORING DALAM PENINGKATAN KUALITAS (TINJAUAN KONSEPTUAL MONITORING SUPERVISI) - Wifdatun Nisa; Rochmat Cahyo Wibowo; Rahmad Rismawan; Fatmah Nur'aeni; Muh Hizbul Muflihin (STKIP Pesisir Selatan, 2026)
This research examines monitoring the outcomes of supervision and educational evaluation through a literature review to understand its role in quality assurance. The review addresses concepts, objectives, functions, implementation processes, and supporting and inhibiting factors of monitoring supervisory results. Findings indicate that monitoring acts as a bridge between supervisory recommendations and classroom implementation and serves as a basis for data‑driven decisions to support teacher professional development and improve learning quality. Monitoring effectiveness is influenced by school leadership, supervisor competence, teacher readiness, availability of resources, and structured follow‑up mechanisms. Effective monitoring requires a collaborative approach, continuity, constructive feedback, and the use of technology for documentation and analysis. The paper concludes that systematic, collaborative, and sustained monitoring can transform supervision from an administrative formality into a professional development mechanism that meaningfully improves teaching and learning. Recommendations include strengthening follow‑up systems, providing supervisory training for school leaders, and conducting empirical studies to test proposed monitoring models.